A Medico-legal Perspective on the Termination of Pregnancies Resulting from Wartime-Rape (Bangladesh Journal of Medical Science, 2020)
The study is designed to investigate the issue of abortion for rape-victims to draw the attentions of Islamic clerics in order to appraise consciousness and outlook of legal edicts within constrain of Islamic bio-medical and bio-ethical norms. For this purpose, a number of Islamic treatises are systematically examined, and a cross-cultural along with a cross-country assessment of 47 countries abortion laws particularly ‘Muslim-majority’ (OIC member) countries are conducted to assess the momentous impacts on rape-victims. Additionally, contemporary data i.e. legal edicts and various reported rape/adultery cases in different Islamic countries are analyzed with special reference to the circumstances in which the verdicts are issued. The study asserts that mostly the classical and contemporary literature silent on the cited issue except few of the legal edicts. Although, Islamic lit and scripts including bio-medical and bio-ethical has discussed it in general way. As a result, the rape victims appeared that they may be allowed termination of unwanted fetus due to coerced sexual relation. But, whether in preview of, some of the legal edicts which causes intricacy, the state laws, rules and more particularly the religious and cultural aspects may allow this kind of deliberation? A predominantly conventional approach was found, since 18 out of 47 countries do not allow abortion except for necessity. Less than 50% of OIC members legally permit abortion on medical grounds. Nevertheless, there was a substantial diversity between Muslim countries. Albeit, a multidimensional viewpoint is very important due to the consequential psychiatric and social problems, since there is an immense need to provide real solutions to such cases that would not contradict Islamic bioethical principles. Therefore, termination of rape resulting pregnancies may be declared valid, provided with specific conditions and guidelines as per Shariah keeping in view bio-medical and bio-ethical norms.Bangladesh Journal of Medical Science Vol.19(3) 2020 p.372-385